A Study on The Impact of Color Consideration and Interior Designing on Patient Satisfaction in IPD of A Multispeciality Hospital in Gujarat - Shabana Parveen Khan; Rahul Sharma; Pinkal Shah (International Journal For Multidisciplinary Research, 2026)
The physical environment of healthcare facilities plays a crucial role in influencing patient outcomes and satisfaction. Among environmental factors, colour consideration and interior design are increasingly recognized for their impact on patients’ psychological well-being, stress levels, and recovery process. However, many hospitals continue to rely on conventional designs, often neglecting evidence-based colour and interior strategies. This study aims to assess the impact of colour consideration and interior designing on patient satisfaction in inpatient departments (IPD), with special reference to gynecology, pediatric, and cardiac wards in a multi-speciality hospital in Gujarat.